Autonomous mapping and navigation for a holonomic robot in an unknown environment - Dumas León, Alejandro; Araujo González, Jorge Tomás; Mendoza Gómez, Eduardo Arturo; Orozco Rosas, Ulises; Picos, Kenia (My University, 2024)
This work presents the development of an autonomous mapping and navigation system tailored for a holonomic robot operating in unknown environments, leveraging Light Detection and Ranging (LiDAR) technology. The core of this research lies in integrating a sophisticated Simultaneous Localization and Mapping (SLAM) algorithm with real-time LiDAR data processing and the GPU’s parallel capabilities to process several subspaces concurrently. This work introduces a novel method to accelerate route planning in an omnidirectional mobile robot fusing advances in hardware with sophisticated algorithmic techniques, a new paradigm is established in path planning for omnidirectional mobile robots, marking an important milestone in the search for more agile and capable robotic systems.
SPIE.DIGITAL LIBRARY
Keywords: Mapping; Navigation; Campus Tijuana